2015
DOI: 10.1371/journal.pone.0144100
|View full text |Cite
|
Sign up to set email alerts
|

The Role of ARX in Human Pancreatic Endocrine Specification

Abstract: The in vitro differentiation of human embryonic stem cells (hESCs) offers a model system to explore human development. Humans with mutations in the transcription factor Aristaless Related Homeobox (ARX) often suffer from the syndrome X-linked lissencephaly with ambiguous genitalia (XLAG), affecting many cell types including those of the pancreas. Indeed, XLAG pancreatic islets lack glucagon and pancreatic polypeptide-positive cells but retain somatostatin, insulin, and ghrelin-positive cells. To further examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 55 publications
3
26
0
Order By: Relevance
“…However the molecular or regulatory features underlying development of these abnormal Glucagon + cells in T1D has not been described, reflecting inherent difficulties of pancreas procurement in humans with specific diseases. The finding of ARX and DNMT1 loss or reduction in Glucagon + Insulin + cells from two subjects with T1D corroborates prior studies in mice and human cell lines suggesting that Arx or Dnmt1 establish and/or maintain α-cell fate and function (Collombat et al, 2003; Collombat et al, 2007; Collombat et al, 2009; Avrahami et al, 2015; Gage et al, 2015). Moreover, the abnormal expression of non α-cell factors such as NKX6.1 and PDX1 in a subset of Glucagon + cells is consistent with prior reports of impaired α-cell function in T1D (Cryer et al, 2003; Pietropaolo et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…However the molecular or regulatory features underlying development of these abnormal Glucagon + cells in T1D has not been described, reflecting inherent difficulties of pancreas procurement in humans with specific diseases. The finding of ARX and DNMT1 loss or reduction in Glucagon + Insulin + cells from two subjects with T1D corroborates prior studies in mice and human cell lines suggesting that Arx or Dnmt1 establish and/or maintain α-cell fate and function (Collombat et al, 2003; Collombat et al, 2007; Collombat et al, 2009; Avrahami et al, 2015; Gage et al, 2015). Moreover, the abnormal expression of non α-cell factors such as NKX6.1 and PDX1 in a subset of Glucagon + cells is consistent with prior reports of impaired α-cell function in T1D (Cryer et al, 2003; Pietropaolo et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…5(i) and 5(j) ]. qRT-PCR analysis utilizing RNA from isolated Casr +/+ and Casr Nuf/Nuf islets revealed that these changes in β -cell and α -cell proliferation were not associated with significant alterations in the expression of genes regulating islet mass such as Foxo1 , Foxm1 , Ngn3 , and Tcf7l2 ( 31 34 ), which promote β -cell proliferation, or in the expression of genes such as Arx and Irx2 ( 35 ), which influence α -cell proliferation ( ).…”
Section: Resultsmentioning
confidence: 99%
“…ARX inactivation is expected to induce stem cell or other mature pancreatic endocrine cell in to insulin-producing cell as an essential factor (Pearl and Horb, 2008). Surprisingly, the experiment in vitro suggests that ARX inhibition does not have obvious effective on the trandifferentiation into b-cells in differentiated human embryonic stem cells using 33-day and7satges protocol or expanded a-cells treated with a combination of solube factors (Gage et al, 2015). However, misactivation of ARX inhibits the redifferentation of ex-vivo expansion of b-cells, elevates insulin mRNA levels and increases the productivity of insulin-positive cells, which suggests ARX blocking could be an effective approach of facilitate the generation of abundant b-cells under defined conditions (Friedman-Mazursky et al, 2016).…”
Section: Expectation and Conclusionmentioning
confidence: 96%